SARS-CoV and emergent coronaviruses: viral determinants of interspecies transmission - Bolles, Meagan (Elsevier B.V., 2011)
Most new emerging viruses are derived from strains circulating in zoonotic reservoirs. Coronaviruses, which had an established potential for cross-species transmission within domesticated animals, suddenly became relevant with the unexpected emergence of the highly pathogenic human SARS-CoV strain from zoonotic reservoirs in 2002. SARS-CoV infected approximately 8000 people worldwide before public health measures halted the epidemic. Supported by robust time-ordered sequence variation, structural biology, well-characterized patient pools, and biological data, the emergence of SARS-CoV represents one of the best-studied natural models of viral disease emergence from zoonotic sources. This review article summarizes previous and more recent advances into the molecular and structural characteristics, with particular emphasis on host–receptor interactions, that drove this remarkable virus disease outbreak in human populations.